THE ROLE OF ESP IN INTERNATIONAL BUSINESS AND NEGOTIATIONS THE CONTRIBUTION OF PRIVATE UNIVERSITIES - Barotov Nurjaxon; Maftuna Nurova (TADQIQOTLAR, 2025)
Annotation: In today’s world, speaking English fluently is essential for conducting business with people from various countries. English for Specific Purposes (ESP) teaches businesspeople how to speak the appropriate English for their jobs. Private universities play an essential role in teaching business people this style of English. They provide specialized classes that educate the language abilities required for business. These private institutions provide students with the tools they need to converse effectively with people from various countries. This is beneficial for firms looking to acquire and sell goods, as well as collaborate with enterprises in other countries. When business professionals speak English fluently, it benefits the country’s economy, trade, and international relations. Private universities promote international business by offering appropriate skills.